4 Effect of Piglet Birth Weight on Post-Natal Changes in Body Temperature. (10th April 2018) - Cooper, N C; Ellis, M; Xiong, Y; Gates, R
Abstract: Low post-natal body temperature is a predisposing factor for piglet mortality. This study investigated the effect of birth weight on piglet body temperature over 24 h after birth under typical conditions. Sows were in crates within a pen (total pen floor area for sow and piglets was 3.52 m 2 ). Room temperature was set at 22.8°C; there was one heat lamp on one side in the middle of the pen. A total of 352 piglets from 35 litters (172 barrows; 180gilts) were used. Piglets were weighed at birth; rectal temperature was measured at birth and 15, 30, 45, 60, 90, 120, 180, and 240 min, and 24 h after birth. Data were divided into birth weight quartiles (Q1: 0.48-1.16 kg, Q2: 1.18-1.42 kg, Q3: 1.44-1.62 kg, Q4: 1.64-2.46 kg). Body temperature data were not normally distributed and were transformed using PROC RANK of SAS (SAS Inst. Inc., Cary, NC); a repeated measures analysis was carried out with PROC MIXED; the model included fixed effects of weight quartile, time of measurement (repeated measure), sow, and gender, and the random effect of farrowing date. Mean weight and rectal temperature at birth were 1.40 ± 0.35kg and 39.0 ± 0.91°C, respectively. Body temperature decreased after birth; the greatest reduction was at 30 min after birth (-4.4 ± 1.61°C lower than birth temperature; P < 0.05 ). Subsequently, temperatures increased but were below ( P < 0.05 ) birth temperature at 240 min and 24 h (-0.9 ± 1.16°C and -0.5 ± 1.04°C, respectively). There was no effect ( P > 0.05) of gender on temperature at any time. Temperature of Q1 was lower ( P < 0.05 ) than that for Q3 and Q4 at most measurement times; temperatures for Q2 were intermediate to but not always different ( P > 0.05 ) from Q1 and Q3. Differences between mean temperature for Q1 and the other quartiles increased from birth (38.8, 39.0, 39.1, and 39.2 for Q1 to Q4, respectively; SEM 0.17; P < 0.05 )) to 90 min after birth (35.3, 36.8, 37.4, and 37.5, respectively; SEM 0.27; P < 0.05 ). Subsequently, differences in mean temperatures between the quartiles decreased but was still lower for Q1 than Q4 at 24 h (38.4, 38.6, 38.8, and 38.9, respectively; SEM 0.08; P < 0.05 ). These results highlight that all piglets experienced decreased body temperature after birth and that the lightest pigs (i.e., ≤1.16 kg birth weight) showed the greatest decrease and the slowest recovery.